Pengelolaan Persediaan Barang Habis Pakai dalam Mendukung Efektivitas Penatausahaan pada BPPKAD Kabupaten Ponorogo - Sandria Bunga Devianti; Nurul Hidayah (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2026)
Abstract This study aims to examine the management of consumable inventory in relation to the effectiveness of inventory administration at the Regional Revenue, Financial Management, and Asset Agency (BPPKAD) of Ponorogo Regency. Consumable inventory constitutes a component of local government current assets and plays a strategic role in supporting administrative operations and public service delivery. This research employs a qualitative descriptive method with a case study approach. Data were collected through document analysis, observation, and limited interviews with parties involved in inventory management. The findings indicate that the management of consumable inventory at BPPKAD of Ponorogo Regency has generally been implemented in accordance with prevailing regional financial management regulations. However, several administrative constraints remain, including an inadequately integrated recording system, delays in data updating, and suboptimal implementation of internal control at the inventory administration stage. These conditions adversely affect the accuracy of inventory data and the effectiveness of reporting. Based on these findings, the study recommends strengthening a digital-based inventory recording system, enhancing interdepartmental coordination, and reinforcing supervisory mechanisms to improve the accountability and effectiveness of consumable inventory administration.